Choosing the optimal climate change policy in the presence of catastrophic risk - Francesco Bosello; Enrica De Cian; Licia Ferranna (European Investment Bank (EIB), 2012)
This paper contributes to the normative literature on mitigation and adaptation by analyzing their optimal policy balance in the context of climate catastrophic risk. The investigation enriches an integrated assessment model introducing the endogenous link between the probability of experiencing a climate-change related catastrophic event, the temperature increase caused by GHG emissions, and ultimately abatement choices. Results indicate that the presence of catastrophic risk induces substantial mitigation effort even in a non-cooperative setting, where usually global cooperation on climate, and accordingly substantive emission reductions, do not succeed. The policy balance is realigned from adaptation toward more mitigation, and the responsiveness of mitigation to changes in adaptation decreases. Compared to a world without climate catastrophes, risk reduces the substitutability between adaptation and mitigation because only mitigation can influence the catastrophic probability. In this setting, our analysis also shows that adaptation funds and strategic unilateral commitments to adaptation are not the most efficient ways of buying emission reduction in less developed countries, though they could create some welfare gains and induce abatement in the recipient countries. – – Mit diesem Arbeitspapier wird ein Beitrag zu den Regelwerken zu den Themenbereichen Bekämpfung des Klimawandels und Anpassung an seine Auswirkungen geleistet, indem analysiert wird, wie das optimale politische Verhältnis dieser beiden Bereiche zueinander angesichts der Gefahr einer Klimakatastrophe aussieht. Die Untersuchung fließt in ein integriertes Bewertungsmodell ein, in dem erstmals der ursächliche Zusammenhang zwischen der Wahrscheinlichkeit, eine durch den Klimawandel bedingte Katastrophe zu erleben, dem Temeraturanstieg aufgrund der Treibhausgasemissionen und schließlich den Beschlüssen zur Emissionsminderung hergestellt wird. Die Ergebnisse deuten darauf hin, dass die vorhandene Gefahr von Katastrophen selbst bei ungünstigen Rahmenbedingungen umfangreiche Maßnahmen zur Bekämpfung des Klimawandels zur Folge hat, auch wenn der weltweiten Zusammenarbeit bei Klimaschutzinitiativen - und somit bei der weitgehenden Verringerung der Emissionen - in der Regel kein Erfolg beschieden ist.
Keywords: C61; D58; Q5; 330; climate change; mitigation; adaptation; climate risk; integrated assessment